A Rare, Strong Shock Front in the Merging Cluster SPT-CLJ 2031-4037 - Purva Diwanji; Stephen A. Walker; M. S. Mirakhor (The Astrophysical Journal, 2024)
We present our findings from the new deep Chandra observations (256 ks) of the merging galaxy cluster SPT-CLJ 2031-4037 at z = 0.34. Our observations reveal intricate structures seen in a major merger akin to the Bullet Cluster. The X-ray data confirm the existence of two shock fronts, one to the northwest and one to the southeast, by directly measuring the temperature jump of gas across the surface brightness edges. The stronger shock front in the northwest has a density jump of 3.16 ± 0.34 across the sharp surface brightness edge and Mach number $M={3.36}_{-0.48}^{+0.87}$ , which makes this cluster one of the rare merging systems with a Mach number M > 2. We use the northwestern shock to compare two models for shock heating—the instant heating model and the Coulomb collisional heating model—and we determine that the temperatures across the shock front agree with the Coulomb collisional model of heating. For the shock front in the southeastern region, we find a density jump of 1.53 ± 0.14 and a Mach number of $M={1.36}_{-0.08}^{+0.09}$ .